Gout. - Sedlacek, Beverly (Journal of Consumer Health on the Internet)
For each issue of Journal of Consumer Health on the Internet, the editor selects three to five health care sites containing high quality health care information on a given subject. The topic for each issue is very much dependent on the whim of the editor and the consumer questions that have crossed her desk. Sites used within the column are chosen based on the editor's personal experience and usage of the Internet. Each select site has been subjected to rigorous evaluation criteria. Evaluation criteria include: reputation of the producer/publisher of the site; bias; content and scope of information provided (including types of information provided – general overviews or specific conditions, treatments, etc.); intended audience (professionals, adults, teens, or children); currency of site updates; and viability of links. Dead links and changing URLs are a problematic reality of Internet usage. The selected sites have exhibited stability in providing long-term access to quality information. Columns begin with a brief discussion of the topic. In addition to the selected sites, other resource sites and URLs may be included in the discussion. Following the discussion, the main page of each select site will be reproduced, including site title and URL for bookmark purposes. The second page will summarize producer information, content, search options, audience, and noteworthy items. JCHI Editor's Select Sites are printed on two facing pages so they can be used as guides beside computer terminals. Web site and topic suggestions for the JCHI Editor's Select Sites column are welcome. Send suggestions to: Nancy R. Glassman, D. Samuel Gottesman Library, Albert Einstein College of Medicine, 1300 Morris Park Avenue, Bronx, NY 10461. E-mail nancy.glassman@einstein.yu.edu